Improvement in coronary haemodynamics after percutaneous coronary intervention: assessment using instantaneous wave-free ratio. - Nijjer, S; Sen, S; Petraco, R; Sachdeva, R; Cuculi, F; Escaned, J; Broyd, C; Foin, N; Hadjiloizou, N; Foale, R; Malik, I; Mikhail, G; et al. (2013)
OBJECTIVE: To determine whether the instantaneous wave-free ratio (iFR) can detect improvement in stenosis significance after percutaneous coronary intervention (PCI) and compare this with fractional flow reserve (FFR) and whole cycle Pd/Pa. DESIGN: A prospective observational study was undertaken in elective patients scheduled for PCI with FFR ≤ 0.80. Intracoronary pressures were measured at rest and during adenosine-mediated vasodilatation, before and after PCI. iFR, Pd/Pa and FFR values were calculated using the validated fully automated algorithms. SETTING: Coronary catheter laboratories in two UK centres and one in the USA. PATIENTS: 120 coronary stenoses in 112 patients were assessed. The mean age was 63 ± 10 years, while 84% were male; 39% smokers; 33% with diabetes. Mean diameter stenosis was 68 ± 16% by quantitative coronary angiography. RESULTS: Pre-PCI, mean FFR was 0.66 ± 0.14, mean iFR was 0.75 ± 0.21 and mean Pd/Pa 0.83 ± 0.16. PCI increased all indices significantly (FFR 0.89 ± 0.07, p<0.001; iFR 0.94 ± 0.05, p<0.001; Pd/Pa 0.96 ± 0.04, p<0.001). The change in iFR after intervention (0.20 ± 0.21) was similar to ΔFFR 0.22 ± 0.15 (p=0.25). ΔFFR and ΔiFR were significantly larger than resting ΔPd/Pa (0.13 ± 0.16, both p<0.001). Similar incremental changes occurred in patients with a higher prevalence of risk factors for microcirculatory disease such as diabetes and hypertension. CONCLUSIONS: iFR and FFR detect the changes in coronary haemodynamics elicited by PCI. FFR and iFR have a significantly larger dynamic range than resting Pd/Pa. iFR might be used to objectively document improvement in coronary haemodynamics following PCI in a similar manner to FFR.